Transmission electron microscopy investigation of semiconductor quantum dots - Liao, X; Zou, J; Cockayne, D (2000)
Transmission electron microscopy was used to study InGaAs/GaAs and Ge(Si)/Si quantum dots. Results on the detailed microstructural investigation using plan-view [001] zone-axis bright-field diffraction contrast imaging technique combined with image simulations are presented.